2019
DOI: 10.1093/mnras/stz112
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of C, N, and Na abundances in red giant stars of the Sculptor dwarf spheroidal galaxy

Abstract: The origin of the star-to-star abundance variations found for the light elements in Galactic globular clusters (GGCs) is not well understood, which is a significant problem for stellar astrophysics. While the light element abundance variations are very common in globular clusters, they are comparatively rare in the Galactic halo field population. However, little is known regarding the occurrence of the abundance anomalies in other environments such as that of dwarf spheroidal (dSph) galaxies. Consequently, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 85 publications
2
20
0
Order By: Relevance
“…Here, the blue and red histograms represent the findings from methods I and III, respectively. For comparison, we indicate the fractions for bound cluster stars as reported by Carretta et al (2009, solid dence for CN-bimodalities amongst the dSph field star populations is sparse (e.g., Smith & Dopita 1983;Lardo et al 2016a;Norris et al 2017;Salgado et al 2019). However, several GCs in the MW have been associated with dwarf-accretion events.…”
Section: The Fraction Of Chemically Altered Stars Amongst Bona-fide Ementioning
confidence: 73%
See 1 more Smart Citation
“…Here, the blue and red histograms represent the findings from methods I and III, respectively. For comparison, we indicate the fractions for bound cluster stars as reported by Carretta et al (2009, solid dence for CN-bimodalities amongst the dSph field star populations is sparse (e.g., Smith & Dopita 1983;Lardo et al 2016a;Norris et al 2017;Salgado et al 2019). However, several GCs in the MW have been associated with dwarf-accretion events.…”
Section: The Fraction Of Chemically Altered Stars Amongst Bona-fide Ementioning
confidence: 73%
“…As a consequence, the number of chemically normal stars that are erroneously classified as 1P stars would be artificially increased, which in turn would lead to a higher N 1P /N tot . Evi- dence for CN-bimodalities amongst the dSph field star populations is sparse (e.g., Smith & Dopita 1983;Lardo et al 2016a;Norris et al 2017;Salgado et al 2019). However, several GCs in the MW have been associated with dwarf-accretion events.…”
Section: The Fraction Of Chemically Altered Stars Amongst Bona-fide E...mentioning
confidence: 99%
“…It has been shown that the most Na-poor limit in dwarf galaxies is lower than the Na abundance of Milky Way field stars, with some exceptions (Colucci et al 2012;Ishigaki et al 2014;Battaglia et al 2017;Villanova et al 2019;Salgado et al 2019;Matsuno et al 2019;Aguado et al 2020). Therefore, first generation stars of globular clusters formed in accreted dwarf galaxies should mostly have Na abundances lower than their counterparts of globular clusters formed in situ, which explains the range of 1G values seen in Figure 1.…”
Section: Analysis and Discussionmentioning
confidence: 89%
“…It has been shown that the most Na-poor limit in dwarf galaxies is lower than the Na abundance of Milky Way field stars, with some exceptions (Colucci et al 2012;Ishigaki et al 2014;Battaglia et al 2017;Villanova et al 2019;Salgado et al 2019;Matsuno et al 2019;Aguado et al 2020). Therefore, first generation stars of globular clusters formed in accreted dwarf galaxies should mostly have Na abundances lower than their counterparts of globular clusters that formed in situ, which explains the range of 1G values seen in Fig.…”
Section: Analysis and Discussionmentioning
confidence: 99%